2021
DOI: 10.2147/ijgm.s336602
|View full text |Cite
|
Sign up to set email alerts
|

Significance of TEAD Family in Diagnosis, Prognosis and Immune Response for Ovarian Serous Carcinoma

Abstract: Purpose: To explore the molecular profiles of transcriptional enhanced associate domain (TEAD) family in ovarian serous carcinoma (OSC). Methods: In this study, we use bioinformatics methods including GEPIA, GE-mini, Oncomine 3.0, Kaplan-Meier plotter, cBioPortal, WebGestalt, TIMER2.0 and DiseaseMeth2.0, and in vitro experimental RT-PCR to assess the expression profiles and prognostic significance of TEAD family in OSC. Results: According to the bioinformatics analysis, TEAD family was abnormally expressed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…54,55 In addition, it is reported that knockdown of TEAD2 in ovarian serous carcinoma (OSC) induces ferroptosis by increasing ROS. 56 We note that metabolic fitness is reduced in TEAD2 and E2A overexpressing cells upon ARR treatment (Figures 6D-6G). Thus, low acetyl-CoA levels may promote tumorigenesis via hypo-acetylation of pluripotency factors and metabolic enzymes.…”
Section: Discussionmentioning
confidence: 82%
“…54,55 In addition, it is reported that knockdown of TEAD2 in ovarian serous carcinoma (OSC) induces ferroptosis by increasing ROS. 56 We note that metabolic fitness is reduced in TEAD2 and E2A overexpressing cells upon ARR treatment (Figures 6D-6G). Thus, low acetyl-CoA levels may promote tumorigenesis via hypo-acetylation of pluripotency factors and metabolic enzymes.…”
Section: Discussionmentioning
confidence: 82%
“…Regarding the TEAD4, cancer cells overexpressing this transcription factor showed immune system process and immune response pathways such as antigen processing and presentation, natural killer cell mediated cytotoxicity, and T cell receptor signaling pathway differentially activated when compared to controls. The differential expression of the TEAD genes family also showed significant association with different types of immune cells infiltration in the tumor environment ( Ren et al, 2021 ; J. Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Next, Venn plots were employed to identify the co-DEGs among the exosome-associated gene dataset (Supplementary Table 1 ) [ 24 ] and the above-mentioned GEO datasets. After then, Xiantao Xueshu [ 25 ], TNMplot [ 26 ], and UALCAN [ 27 ] were used to confirm the downregulated expression levels of ENPP1 in LIHC tissues.…”
Section: Methodsmentioning
confidence: 99%